Questionnaires as interventions: can taking a survey increase teachers' openness to student feedback surveys?. Issue 3 (16th March 2018) - Gehlbach, Hunter; Robinson, Carly D.; Finefter-Rosenbluh, Ilana; Benshoof, Chris; Schneider, Jack
Abstract: Administrators often struggle in getting teachers to trust their school's evaluation practices – a necessity if teachers are to learn from the feedback they receive. We attempted to bolster teachers' support for receiving evaluative feedback from a particularly controversial source: student-perception surveys. For our intervention, we took one of two approaches to asking 309 teachers how they felt about students evaluating their teaching practice. Control participants responded only to core questions regarding their attitudes towards student-perception surveys. Meanwhile, treatment participants were first asked whether teachers should evaluate administrators in performance reviews and were then asked the core items about student-perception surveys. Congruent with cognitive dissonance theory, this juxtaposition of questions bolstered treatment teachers' support for using student surveys in teacher evaluations relative to the control group. We discuss the implications of these findings with respect to increasing teacher openness to alternative evaluation approaches, and consider whether surveys show promise as a vehicle for delivering interventions.